Implementasi Pendidikan Kesehatan tentang Imunisasi Berbasis Aplikasi iPosyandu terhadap Pengetahuan Ibu Balita : Implementation of Health Education on Immunization Based on iPosyandu Application toward Knowledge of Mothers with Toddlers - Susanti, Ari Indra; Harahap, Hasrina Hidayati; Rinawan , Fedri Ruluwedrata; Muaebah, Shiva (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
During the 19 Pandemic Covid period, mother was worried and afraid to bring their babies to healthcare facilities. For this reason, parents play an active role in achieving immunization, and the importance of knowledge is equipped with immunization during the COVID-19 pandemic. Therefore, This community service activity aims to increase mothers' knowledge about immunization through educational media through videos accessed from the iPosyandu application. Methods for implementing this community service activity include making educational videos, coordinating with cadres and mothers who have babies and toddlers for the implementation of health education, as well as conducting evaluations using pre-tests and post-tests in the form of Google forms shared via WhatsApp groups of mother of toddlers. The result of this activity is an increase in mothers' knowledge about immunization from 5,50% to 80,80% good knowledge after watching educational videos through the iPosyandu application for parents. Suggestions for village cadres and midwives to optimize educational media in the iPosyandu application to provide health information to mothers with babies and toddlers.